Precise Pose Alignment through the Combined Method of Differential Evolution and Simplex Algorithm - Jian Gao; Liangsheng Xu; Yueping Chen; Xin Chen; Detao Zheng (Institute of Advanced Engineering and Science, 2013)
In reverse engineering applications, there is a problem of precise alignment from measured data to a CAD model. This paper presents a new method where the measurement points can be precisely aligned with its corresponding CAD model. Initially, the measured data is aligned approximately through a least-square method with the minimum distance principle. Based on this initial alignment result, the precise alignment is completed through the Differential Evolution (DE) algorithm and the Simplex method. The experimental results show that the alignment algorithm proposed in this paper possesses an accuracy of 0.055m and spending less processing time than the genetic algorithm. Therefore, the proposed method is effective for the measured data alignment to the original surface model. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2310